MAP2 phosphorylation: mechanisms, functional consequences, and emerging insights - Jiali Lyu; Jiali Lyu; Andrew G. DeMarco; Robert A. Sweet; Robert A. Sweet; Robert A. Sweet; Melanie J. Grubisha; Melanie J. Grubisha (Frontiers in Cellular Neuroscience)
Microtubule-associated protein 2 (MAP2) is a key regulator of cytoskeletal dynamics and neuronal function. It stabilizes microtubules, shapes dendrites, influences synaptic plasticity, and regulates transportation and protein synthesis through its interactions with other proteins. MAP2 undergoes extensive phosphorylation, which dynamically modulates these interactions and alters MAP2 functions. This review provides a comprehensive overview of MAP2 structure, its diverse functional roles in neurons, the kinases that regulate its phosphorylation. We highlight how phosphorylation by Src family kinases, proline-directed kinases, MARK, PKA, PKC, and CAMKII governs MAP2’s role in cytoskeletal organization, protein chaperone activity, and dendrite outgrowth.